Targeting Energy Expenditure-Drugs for Obesity Treatment - Carlos M. Jimenez-Munoz; Marta López; Fernando Albericio; Kamil Makowski (MDPI AG, 2021)
Obesity and overweight are associated with lethal diseases. In this context, obese and overweight individuals infected by COVID-19 are at greater risk of dying. Obesity is treated by three main pharmaceutical approaches, namely suppressing appetite, reducing energy intake by impairing absorption, and increasing energy expenditure. Most compounds used for the latter were first envisaged for other medical uses. However, several candidates are now being developed explicitly for targeting obesity by increasing energy expenditure. This review analyzes the compounds that show anti-obesity activity exerted through the energy expenditure pathway. They are classified on the basis of their development status: FDA-approved, Withdrawn, Clinical Trials, and Under Development. The chemical nature, target, mechanisms of action, and description of the current stage of development are described for each one.